Bringing Javanesse Traditional Dance into Basic Physics Class: Exemplifying Projectile Motion through Video Analysis. (August 2016) - Handayani, Langlang; Aji, Mahardika Prasetya; Susilo,; Marwoto, Putut
Abstract: An alternative approach of an arts-based instruction for Basic Physics class has been developed through the implementation of video analysis of a Javanesse traditional dance: Bambangan Cakil . A particular movement of the dance -weapon throwing- was analyzed by employing the LoggerPro software package to exemplify projectile motion. The results of analysis indicated that the movement of the thrown weapon in Bambangan Cakil dance provides some helping explanations of several physics concepts of projectile motion: object's path, velocity, and acceleration, in a form of picture, graph and also table. Such kind of weapon path and velocity can be shown via a picture or graph, while such concepts of decreasing velocity in y direction (weapon moving downward and upward) due to acceleration g can be represented through the use of a table. It was concluded that in a Javanesse traditional dance there are many physics concepts which can be explored. The study recommends to bring the traditional dance into a science class which will enable students to get more understanding of both physics concepts and Indonesia cultural heritage.